Analysis of the risk of climate hazards to the airport system - Voskaki, Asimina (Cranfield University, 2025)
Climate hazards are increasingly disrupting the normal functioning of airports worldwide, leading to damage, operational disruptions, safety concerns, economic loss and broader business, environmental and social impacts. Climate extremes such as storms, precipitation, and heat waves are increasing in occurrence and magnitude. As the Earth warms, these threats are only set to grow, placing additional stress on airport infrastructure and current operating practices. While airports make efforts to mitigate risks, a critical gap remains in understanding the scale and complexity of climate hazards, especially lower frequency, high-impact events that typically have the highest potential for causing disruption. Current risk analysis practices and tools often fail to account for these complexities. This research investigates the impact of climate hazards on airports and how current risk management practices address these challenges. In doing so, it introduces a new framework for analysing the risk of climate hazards to airport systems, the Airport Climate Risk Index (ACRI). The ACRI is a composite indicator addressing climate hazards, including flooding (coastal and inland), extreme temperatures, storms, wind, heavy snowfall, and drought/water scarcity. The index, designed as a self-assessment tool, seeks to empower airports to identify, analyse, and assess their risks related to climate hazards. The validation of the tool was carried out at four regional airports in the UK, providing insights into current practices and challenges in managing climate hazards within existing frameworks. The research findings reveal a need for a change in practices to improve regional airports' preparedness for climate-resilient development. Existing mitigation measures must be evaluated for their effectiveness in addressing the increasing intensity and variety of climate hazards. A more proactive approach is essential for integrating climate-related risks into long-term planning, infrastructure development, and investment decisions. Building more adaptability within the airport elements appears necessary to enable the regional airports to grow sustainably.
Keywords: airports; climate hazards; climate risk; climate adaptation; climate change